2003
DOI: 10.1359/jbmr.2003.18.6.960
|View full text |Cite
|
Sign up to set email alerts
|

High Bone Mass in Mice Expressing a Mutant LRP5 Gene

Abstract: A unique mutation in LRP5 is associated with high bone mass in man. Transgenic mice expressing this LRP5 mutation have a similar phenotype with high bone mass and enhanced strength. These results underscore the importance of LRP5 in skeletal regulation and suggest targets for therapies for bone disease.A mutation (G171V) in the low-density lipoprotein receptor related protein 5 (LRP5) has been associated with high bone mass (HBM) in two independent human kindreds. To validate the role of the mutation, several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
375
4
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(405 citation statements)
references
References 47 publications
(78 reference statements)
21
375
4
3
Order By: Relevance
“…Conversely, mice that overexpress the G171V LRP5 mutant, have a high bone mass phenotype (Babij et al, 2003). Unlike homozygous mutants, heterozygous Dkk1 ĂŸ /À mice are viable and they show an increase in bone mineral density (Morvan et al, 2006).…”
Section: Dkk1 and 2 In Bone Formationmentioning
confidence: 99%
“…Conversely, mice that overexpress the G171V LRP5 mutant, have a high bone mass phenotype (Babij et al, 2003). Unlike homozygous mutants, heterozygous Dkk1 ĂŸ /À mice are viable and they show an increase in bone mineral density (Morvan et al, 2006).…”
Section: Dkk1 and 2 In Bone Formationmentioning
confidence: 99%
“…On the other hand, gain‐of‐function mutations of LRP5 are associated with a high bone mass phenotype 117, 118. Interestingly, no change in osteoblast activity was observed in mice with increased expression of LRP5 119. These mice did, however, have decreased osteoblast apoptosis, suggesting that the high bone mass phenotype is because of increased osteoblast cell count rather than function.…”
Section: Implication Of Canonical Wnt Signaling In Vcmentioning
confidence: 99%
“…The converse is found in patients with dominant "gain-of-function" mutations in LRP5 which exhibit abnormally high bone density [7,8]. A transgenic mouse model carrying a human LRP5 high bone mass mutation exhibited significant increases in bone density and mechanical properties [9,10]. Studies have shown that removing one Lrp6 copy from Lrp5 −/− mice increases the osteoporosis severity, suggesting that both LRP5 and LRP6 are critical determinants of bone mass [11].…”
Section: Introductionmentioning
confidence: 99%